Khairul Jasmi's Women's Novel Violence towards Women That Previously Else: Sara Mills' Model - Yesdia Talakua; Hartono (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
The research entitled "Violence Against Women in the Novel Women Preceding the Age by Khairul Jasmi: Sara Mills' Model". The problem examined in this study is how the position of the subject-object and the position of the reader in describing women in the novel Woman Yang Preceded by Khairul Jasmi. The purpose of this research is to describe, analyze, identify, interpret and conclude about the position of the subject-object and the position of the reader in describing women in Khairul Jasmi's novel Perempuan Yang Predating The Age. The results of this study are in the form of the position of the subject or narrator described in the novel Women Who Preceded the Age are Rahmah, Sa'adah, Upik Hitam, Jamilah, Niara and the position of the object or narrated are Minangkabau women, the events that occur in the novel are the descriptions of victims of acts of violence, injustice, and women's resistance, which in this case are women. The reader's position is included to feel what the character Rahmah feels, how she is worried about the fate of herself and the women in the Minangkabau area who often experience acts of violence.